2018
DOI: 10.3201/eid2405.171802
|View full text |Cite
|
Sign up to set email alerts
|

Heartland Virus and Hemophagocytic Lymphohistiocytosis in Immunocompromised Patient, Missouri, USA

Abstract: Heartland virus is a suspected tickborne pathogen in the United States. We describe a case of hemophagocytic lymphohistiocytosis, then death, in an immunosuppressed elderly man in Missouri, USA, who was infected with Heartland virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
0
26
0
2
Order By: Relevance
“…Basic demographic data on the ten published cases indicated that all were male, aged over 50 years and with significant outdoor exposure and nine of the ten cases reporting the removal of a tick prior to onset of illness. Several of the reported cases had medical comorbidities including one immunocompromised patient with a history of rheumatoid arthritis on prednisone, methotrexate, and adalimumab who developed hemophagocytic lymphohistiocytosis . To our knowledge, this is the first published reported case of Heartland virus affecting a solid organ transplant recipient.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Basic demographic data on the ten published cases indicated that all were male, aged over 50 years and with significant outdoor exposure and nine of the ten cases reporting the removal of a tick prior to onset of illness. Several of the reported cases had medical comorbidities including one immunocompromised patient with a history of rheumatoid arthritis on prednisone, methotrexate, and adalimumab who developed hemophagocytic lymphohistiocytosis . To our knowledge, this is the first published reported case of Heartland virus affecting a solid organ transplant recipient.…”
Section: Discussionmentioning
confidence: 90%
“…Heartland virus, first identified as a human disease pathogen in 2009, is an emerging tick‐borne phlebovirus transmitted by Amblyomma americanum or the lone star tick . To date, CDC have diagnosed >40 cases of HRTV with ten of these cases reported in the literature including four deaths . Basic demographic data on the ten published cases indicated that all were male, aged over 50 years and with significant outdoor exposure and nine of the ten cases reporting the removal of a tick prior to onset of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a separate case of an SFTS patient who also had no previous cardiac issues was reported to have fulminant myocarditis caused by SFTSV infection [60]. Immunohistochemical staining for SFTSV or HRTV antigen showed antigen (N protein) positive cells in atypical lymphoid cells of systemic lymph nodes and the spleen of both SFTS or HRTV disease patients [40,[56][57][58][59]61]. Studies of parenchymal cells of various organs from SFTS patients did not show SFTSV antigen present [39,[56][57][58]61].…”
Section: Pathologymentioning
confidence: 97%
“…The degree of HLH is likely correlated with severity of disease, since hemophagocytosis causes thrombocytopenia and lymphopenia due to the engulfment of platelets and lymphocytes, respectively. Several reports also suggested the involvement of HLH in the CNS disorder seen in SFTS patients [39,40,43,56,58,59,61,62]. It has been known that the over-production of pro-inflammatory cytokines resulting in systemic inflammatory response syndrome (SIRS) in SFTS patients leads to the overactivation of T-cells and macrophages, causing HLH and clinical disease in patients [63]; the cytokine and chemokine profiles seen in SFTS patients and their potential role in HLH and disease severity are discussed in detail in Section 4.…”
Section: Pathologymentioning
confidence: 98%
See 1 more Smart Citation